Laparoscopic Management of a Frameless Intrauterine Device-GyneFix Embedded in the Mesentery of the Ileum - Canda, Mehmet Tunç; Demir, Namık (Gynecology Obstetrics & Reproductive Medicine, 2017)
GyneFix® is a small, frameless, armless, flexible intrauterine device. The proximal end contains a knot that is anchored in the uterine fundus using a special apparatus. A 31-year-old woman presented with abdominal cramps ten days after GyneFix® insertion. Transvaginal ultrasonography was unsuccessful in locating the intrauterine device therefore a direct X-ray sonogram of the abdomen while standing was performed. The X-ray sonogram of the abdomen showed the intrauterine device in the right quadrant. An exploratory laparoscopy was performed and showed that the intrauterine device perforated the uterine fundus and was embedded in the mesentery of the ileum. The intrauterine device was removed without complication. Although the reported complication rates are very low for GyneFix®, practitioners should be well trained and should be aware of such complications that could lead to bowel resection. We report the first case of a GyneFix®- Intrauterine device presenting with uterine perforation and nearly intestinal perforation since its recent introduction into the Turkish market.